The European order for payment procedure: Is it an agile and economical process for claiming uncontested cross-border credits? - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The aim of this paper is the study of the European payment order process. The European order for payment procedure was the first uniform procedure created by the European legislator. The objective of Regulation (EC) No. 1896/2006, which establishes this process, was to speed up the claim, and therefore, the collection of cross-border credits in principle uncontested by the debtor. That is, credits that the debtor does not discuss but does not pay either. In these almost fourteen years since the European order for payment procedure was applied, it can be noted that it has been a process that has allowed European creditors to collect millions of euros in debts. However, there is still a long way to go before the true potential of this process is achieved, since the involvement of the Member States in the development of this process has been uneven. In this way, throughout the paper we will analyze the origins of the European order for payment process, each of its phases, as the resolutions of the CJEU has been an important way to clarify aspects in which the legislator had left unfinished and we will highlight aspects that should still be modified in subsequent revisions of the Regulation.